IBM z/OS DFSMShsm Primer - Lovelace, Mary; Biondo, Jose; Erdmann, Derek; Laumann, Gert; Tout, Jacqueline; Truong, Hien; Vangsness, Jeannie; Vernon, Craig (IBM Redbooks, 2013)
DFSMShsm provides space, availability, and tape mount management functions in a storage device hierarchy for both system-managed, and non-system-managed storage environments. DFSMShsm allows you to automate your storage management tasks, improving the productivity by effectively managing the storage devices. This IBM® Redbooks® publication provides technical storage specialists and storage administrators with the basic DFSMShsm knowledge for implementing and customizing DFSMShsm at the IBM z/OS® V1.13 level. Hints and tips about the daily operation, monitoring, and tuning are included. Sysplex environment considerations are also included. If you are implementing DFSMShsm for the first time, you will find valuable information for exploiting the DFSMShsm functions. If you are experienced, you will find that this publication can be used as an update to the latest DFSMShsm functions, and it shows how to use those functions in an existing DFSMShsm installation.
Online resource; Title from title page (viewed December 12, 2013)
Keywords: Electronic data processing -- Backup processing alternatives; Data recovery (Computer science); Information storage and retrieval systems; Sauvegarde (Informatique); Récupération des données (Informatique); Systèmes d'information; Electronic data processing; Backup processing alternatives